1999
DOI: 10.1590/s1516-31801999000600007
|View full text |Cite
|
Sign up to set email alerts
|

Enteric parasites and AIDS

Abstract: Amongst the causes of diarrhea in developing countries, those of a parasitic origin are prominent in patients with AIDS.Opportunistic infections caused by intestinal parasites also vary according to the geographical area and the endemic levels in each location.The progressive decline of immunological and mucous defense mechanisms predisposes patients to early, intermediary and late gastrointestinal manifestations of HIV infection. 6 At later stages of the disease, the alterations in non-specific defense mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
30

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 64 publications
2
23
0
30
Order By: Relevance
“…According to these authors, intestinal parasites were detected in 63.9% of patients from the pre-HAART era and 24% in the HAART era, thus showing a reduction in prevalence between the two periods. Cimerman et al (2,12) found a prevalence of 24.4% for opportunistic parasites in the pre-HAART era and 6.8% after HAART introduction, with higher rates in patients with CD4 + T cells < 200/mm 3 . When comparing periods before and after HAART implementation, Nobre et al (13) observed prevalences of 2.8% and 1.1%, respectively, low in both eras, but even lower after HAART use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these authors, intestinal parasites were detected in 63.9% of patients from the pre-HAART era and 24% in the HAART era, thus showing a reduction in prevalence between the two periods. Cimerman et al (2,12) found a prevalence of 24.4% for opportunistic parasites in the pre-HAART era and 6.8% after HAART introduction, with higher rates in patients with CD4 + T cells < 200/mm 3 . When comparing periods before and after HAART implementation, Nobre et al (13) observed prevalences of 2.8% and 1.1%, respectively, low in both eras, but even lower after HAART use.…”
Section: Discussionmentioning
confidence: 99%
“…Since the emergence of AIDS, clinical alterations related to the gastrointestinal tract have been highly prevalent, of which diarrheic conditions associated to parasitic infections are noteworthy (2). Many studies have shown that some intestinal parasites were frequently associated with severe diarrhea in HIV patients, both in developed and developing countries (2)(3)(4)(5)(6)(7)(8). Socioeconomic and cultural factors have carefully been studied for the impact that they may have on the onset of enteroparasitosis in general and in HIV-infected patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…A freqüência significativamente mais baixa de contaminação nas hortas em relação aos demais pontos de venda pode ser justificada por constituir o ponto inicial da cadeia de comércio e, principalmente, pelo programa de fiscalização de hortas implantado no município há 3 anos 34 . A presença da forma trofozoíta de Giardia sp sugere que a contaminação tenha sido evento recente, provavelmente por manipulação 29 no ponto de venda, visto ser esta forma muito frágil, não sobrevivendo por mais de 15 a 20 minutos no meio externo 7 . Constatamos vários sorotipos de Salmonella cuja importância não se restringe a quadros de gastrenterite mas também, como potenciais agentes causais de grave bacteremia 31 e de meningite resistente a múltiplos antibióticos 9 .…”
Section: Irregularidadesunclassified
“…Since the beginning of the AIDS pandemic, opportunistic infections have been recognized as common complications of the HIV infection 8,29 . The rapid dissemination of this virus contributed to the increasing prevalence of opportunistic protozoa among HIV-infected patients, with Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%